EP309/#952 Archipelago of ovarian cancer research: a dutch nationwide, interdisciplinary ovarian cancer research infrastructure. (4th December 2022) - Zelisse, Hein; Mom, Constantijne; Gent, Mignon Van
Abstract : Objectives: High-impact fundamental and translational research is urgently needed to improve survival of ovarian cancer patients. Therefore, we established the Dutch nationwide Archipelago of Ovarian Cancer Research (AOCR). This multicenter, interdisciplinary infrastructure and biobank is a collaboration between all 19 Dutch hospitals in which ovarian cancer surgery takes place, and is aimed at facilitating large-scale, high-quality fundamental and translational ovarian cancer research. Methods: Adult patients with (suspected) ovarian cancer are eligible for inclusion in the AOCR. Preoperative and follow-up blood samples, ascites, biopsies, and tissue from primary and metastatic tumor sites are collected and stored in a uniform matter for future (genetic) research. One representative histological hematoxylin and eosin stained slide per participant is digitized and reassessed by a gynecological pathologist's panel. Clinical and pathological parameters are retrieved from Dutch data registries. Besides issue of samples to individual researchers and research groups, subsequent research questions will be defined jointly by all collaborators. Results: Between January 2021 and May 2022, 273 patients were included in five participating hospitals. Ten more hospitals are expected to start inclusion between May and July 2022. From these 273 patients, 775 blood samples, 572 tissue samples and 162 digital slides were collected. Conclusions: The AOCR ensures a large collection of samples to be used for research. It enhances interdisciplinary and multicenter collaboration at a national, and, hopefully in the future, international level. The AOCR facilitates large-scale, high-quality fundamental and translational ovarian cancer research with the ultimate aim to improve diagnostics, treatment and survival of ovarian cancer patients.